Mathematical Creativity Through Open-Ended Problems on Linear Equation One Variable - Nathania Lestari; Sugiatno Sugiatno; Dian Ahmad (Universitas Syiah Kuala, 2025)
In solving problems and generating new ideas in mathematics, creativity is needed. However, the facts in Indonesia show that students' mathematical creativity is still in the low category. This situation is suspected because in Indonesia, students are less accustomed to solving open-ended problems to train their thinking skills. In addition, the availability of open-ended problems is still limited, making it difficult for teachers to provide open-ended problems for students. This research produced valid and practical open-ended questions to measure and even improve students' mathematical creativity. The research method applied was formative research development model (preliminary, self evaluation, prototyping, field test). Field test was conducted on 32 students of class VIII SMP Negeri 1 Sungai Raya. The developed open-ended questions successfully measured students' mathematical creativity on fluency, flexibility, and novelty indicators. The development results showed that the open-ended questions made were valid and practical, with 96.875% of students reaching the positive category towards the developed open-ended questions. Thus, the designed open-ended questions function well in measuring and even improving students' mathematical creativity.